Public Diplomacy: A Pragmatic View on the Variety of Actual Experience - K. Borishpolets (Международная аналитика)
Public diplomacy as a phenomenon of international affairs has many formats, and various actors of world politics differently utilize it. The public diplomacy experience of two modern integration projects – the CIS and EEU is of considerable general interest as it is focused on strengthening multilateral positive interaction and not directed to the creation of only one country’s attractiveness. In the context of cultural cooperation, youth policy, educational cooperation, promotion of foreign policy initiatives, work with diaspora, Russia and its partners increasingly use public diplomacy resources. Activity of Post-Soviet integration participants creates unique effect of complementarity of their efforts in the sphere of humanitarian cooperation. That is increasingly needed in establishing dialogue platforms with participation of state and non-state actors within not only CIS and EEU countries, but also their regional environment.